Formation of water-soluble organic matter through fungal degradation of lignin. (September 2019) - Khatami, Seyyedhadi; Deng, Ying; Tien, Ming; Hatcher, Patrick G.
Highlight: ESI-FTICR-MS analysis opens a new window for examining the fate of lignin in nature. Fungal degradation is important in soil humification, transforming lignin to aliphatic molecules. A similarity in biotic and abiotic oxidation of lignin to create new molecules is observed. Abstract: Lignin is a major component of decaying terrestrial vegetation in soils and has been reported to contribute substantially to the formation of soil carbon humus and associated water extracts of soil. To better understand this process of humification, lignin from brown-rot degraded wood was subjected to a white-rot fungus ( Phanerochaete chrysosporium) whose enzymes are particularly effective in lignin degradation. This enzymatic attack was monitored by ultrahigh resolution mass spectrometry of water soluble extracts of the fungal cultures. The molecular level characterizations showed that the P. chrysosporium fungi induced aromatic ring oxidations followed by ring opening, as expected. However, the production of new molecules, some of which are aliphatic, was also observed. These results are consistent with recent findings that hydroxyl radical attack of lignin involves ring opening reactions followed by electrocyclic condensations combined with radical scavenging/disproportionation reactions.